Targeting DNA Binding for NF-κB as an Anticancer Approach in Hepatocellular Carcinoma - Chung, Po Yee (Cells, 2018)
Quinoline core has been shown to possess a promising role in the development of anticancer agents. However, the correlation between its broad spectrum of bioactivity and the underlying mechanism of actions is poorly understood. The present study, with the use of bioinformatics approaches, reported a series of designed molecules which integrated quinoline core and sulfonyl moiety, with the objective of evaluating the substituent and linker effects on anticancer activities and associated mechanistic targets. We identified potent compounds (1h, 2h, 5 and 8) exhibiting significant anticancer effects towards liver cancer cells (Hep3B) with the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) relative values of cytotoxicity below 0.40, a value in the range of doxorubicin positive control with the value of 0.12. Bulky substituents and the presence of bromine atom, as well as the presence of sulfonamide linkage, are likely the favorable structural components for molecules exerting a strong anticancer effect. To the best of our knowledge, our findings obtained from chemical synthesis, in vitro cytotoxicity, bioinformatics-based molecular docking analysis (similarity ensemble approach, SEA),and electrophoretic mobility shift assay provided the first evidence in correlation to the anticancer activities of the selected compound 5 with the modulation on the binding of transcription factor NF-κB to its target DNA. Accordingly, compound 5 represented a lead structure for the development of quinoline-based NF-κB inhibitors and this work added novel information on the understanding of the mechanism of action for bioactive sulfonyl-containing quinoline compounds against hepatocellular carcinoma.